2018
DOI: 10.1002/gj.3323
|View full text |Cite
|
Sign up to set email alerts
|

Structures, strain analyses, and 40Ar/39Ar ages of blueschist‐bearing Heilongjiang Complex (NE China): Implications for the Mesozoic tectonic evolution of NE China

Abstract: The high‐pressure Heilongjiang Complex belongs to a Jurassic accretionary complex in Yilan area, NE China. The complex is located in the junction of three orogenic systems in the NE Asia: the E‐W‐striking Central Asian Orogenic Belt (CAOB), the N‐S‐striking Paleo‐Pacific system, and the ENE‐WSW‐striking Mongol‐Okhotsk system. Thus, a detailed tectono‐metamorphic analysis coupled with accurate radiometric dating of the Heilongjiang Complex provided in this study represent important evidence for understanding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 60 publications
0
8
0
6
Order By: Relevance
“…The youngest metamorphic rock which protoliths are OIB igneous rocks yielded the age of ~140 Ma and ~180 Ma (Zhu et al, 2017a, b). Syntectonic mica Ar-Ar ages are distributed in ~140 Ma and ~160-180 Ma (Wu et al, 2007;Li et al, 2009Li et al, , 2011Aouizerat et al, 2019), these evidences limit the closure time of the Mudanjiang Ocean in the Middle Jurassic to Early Cretaceous. Ge et al (2017) reported that the oldest MORB-type rock was the Late Permian and OIB-type rocks was the Early Permian.…”
Section: Paleozoic Tectonic Evolution History Of Mudanjiang Suture Zonementioning
confidence: 84%
See 1 more Smart Citation
“…The youngest metamorphic rock which protoliths are OIB igneous rocks yielded the age of ~140 Ma and ~180 Ma (Zhu et al, 2017a, b). Syntectonic mica Ar-Ar ages are distributed in ~140 Ma and ~160-180 Ma (Wu et al, 2007;Li et al, 2009Li et al, , 2011Aouizerat et al, 2019), these evidences limit the closure time of the Mudanjiang Ocean in the Middle Jurassic to Early Cretaceous. Ge et al (2017) reported that the oldest MORB-type rock was the Late Permian and OIB-type rocks was the Early Permian.…”
Section: Paleozoic Tectonic Evolution History Of Mudanjiang Suture Zonementioning
confidence: 84%
“…Because the blue schist in this unit is a significant sign of orogenesis, it has clockwise P-T-t paths (Bai et al, 1988;Zhang, 1992;Zhou et al, 2009;Zhao et al, 2010;Li et al, 2010Li et al, , 2014, researchers gradually realized that Heilongjiang complex is a tectonic melange, which is the product of the combination of Songliao and Jiamusi blocks (Cao et al, 1992;Zhang, 1992;Ye et al, 1994). There are many viewpoints on the assemblage time reflected by the Heilongjiang Complex, including Proterozoic (Cao et al, 1992), Early Paleozoic (Xie et al, 2008) and Late Paleozoic (Li et al, 2009), but a lot of recent chronological evidence indicates that the final assemblage time of the two blocks should be Middle Jurassic to Early Cretaceous (Wu et al, 2007;Zhou et al, 2009;Li et al, 2009Li et al, , 2011Zhu et al, 2017a, b, c;Aouizerat et al, 2019). Early Paleozoic syn-and post-orogenic granitoids Wang et al, 2012;Wang et al, , 2017 along both sides of the Mudanjiang suture zone and Devonian strata (Meng et al, 2010;Li et al, 2019) with similar age composition of detrital zircons show the possibility that Songliao and Jiamusi blocks were once integrated during the Paleozoic.…”
mentioning
confidence: 99%
“…Юрские метаморфизованные терригенные породы (а местами -серпентиниты) составляли, по-видимому, матрикс меланжа, а карбон-пермские и триасовые метабазальты, как и ассоциирующие с ними метаморфизованные кремни и карбонатные породы, образовали глыбы и пластины в этом меланже. Прямые подтверждения таких взаимоотношений наблюдались в карьерах около г. Илан, где слюдистые сланцы содержат глыбы и пластины голубых сланцев, амфиболитов и кварцитов размером от долей метра до 200 м [21]. Кроме того, в Хейлунцзянском комплексе присутствуют монцогранитовые жилы адакитового типа с возрастом 175-161 млн лет [22].…”
Section: Cостав и геодинамическая природа хейлунцзянского комплексаunclassified
“…Метаморфиты комплекса Хейлунцзян обнаруживают следы интенсивнейших многоэтапных деформаций. Как показали исследования [21,72,77], сланцеватость метаморфитов, отвечающая заключительному этапу деформаций, имеет стабильное ВСВ (60-90°) простирание, то есть ориентирована практически ортогонально по отношению к меридиональному Муданьцзянскому разлому. Углы падения сланцеватостиот относительно пологих (20-45°) до вертикальных; не исключены и опрокинутые залегания.…”
Section: особенности раннемеловых дислокаций хейлунцзянского комплексаunclassified
“…Together with the geochronological data, it is suggested that the final subduction/collision between the Jiamusi and Songliao blocks took place in the Jurassic, triggered by the Palaeo‐Pacific subduction system. Meanwhile, Aouizerat et al () carried out a detailed structural analysis and 40 Ar– 39 Ar dating of the blueschist for the Heilongjiang Complex which suffered three phases of deformation with 40 Ar– 39 Ar plateau ages on muscovite and phengite of 173–177 Ma interpreted as a cooling age. Finally, they suggested that the westward‐oriented subduction and exhumation fabrics of the high‐pressure Heilongjiang accretionary complex, followed by N–S‐directed upright folding, are interpreted to reflect transition from E–W Pacific subduction regime to N–S‐directed shortening related to the closure of the Mongol–Okhotsk Ocean in the north‐west.…”
Section: Tectonics Of Eastern Chinamentioning
confidence: 99%